AUTONOMOUS VOCABULARY LEARNING FOR READING SKILL IMPROVEMENT: LEXICALLY-BASED TASK AT MTS. ANNAJAH WEST LOMBOK-NTB - Jupri (LPPM Institut Pendidikan Nusantara Global, 2022)
This study was intended to provide a contribution to the improvement of students’ vocabulary mastery in MTs. Annajah Sesela, Gunungsari District, West Nusa Tenggara Province. Based on a preliminary study, the researcher found that this class lack vocabulary mastery in English and the mean score was 54. As the school is Islamic-based, students learn Arabic language very often yet English is only learnt at school. The teachers seldom applied various activities in teaching English. English is not seen as individual words but collocation and colligation. To cope with those problems, the researcher employed Autonomous Vocabulary Learning Strategy through Lexically Based-Task. This study was an action research and designed to increase students’ vocabulary mastery and to improve their reading ability using Autonomous Vocabulary Learning through Lexically Based-Task at MTs. Annajah, Sesele, Gunungsari, West Lombok. This study was conducted in one cycle consisting of eight meetings using the following procedures: planning, implementing, observing, and reflecting. The data of the study were collected through the result of the test, observation checklists, and field notes. The subjects were 30 students of the 2nd grade of MTs. Annajah Sesela, Gunungsari, West Lombok. The procedures of the study were implemented through four steps: (1) the students did extensive reading and searched ten lexicons, (2) the students reported the lexicons along with their lexico-grammatical units to share with the class, (3) the students wrote the lexicons and the sentences on the whiteboard while the audience recorded their friends’ lexicons, (4) the teacher provided feedback for any grammatical errors and assessment was done without scoring to help them achieve the indicators of the instruction. The findings of the study indicated that the Autonomous Vocabulary Learning strategy was successful in increasing students’ vocabulary mastery and improving students’ reading ability. This could be seen from the result of mean score from the tests. The researcher found that the mean score of preliminary tests was 54.17 and the final test was 78.08. It indicated that the mean score of the final test is higher than that of preliminary test (78.08 > 54.17). More than 80% students gained 70 and the total of the students’ lexicons found during this investigation was 300 words. It is suggested that English teachers apply this strategy to increase students’ vocabulary mastery in supporting their reading ability. For the institution, it has to utilize more creative methods in encouraging the students to learn English. And for future researchers, the findings of the research can become a good reference to conduct better research.